Evaluations on numerical simulations of ozone dry deposition over the Yangtze River Delta1. (1st July 2023) - Xu, Jingxin; Wang, Sheng; Mai, Borui; Zheng, Youfei; Qiu, Shuang; Tian, Wenxin; Kang, Hanqing; Zhang, Xi; Gao, Jinhui
Abstract: Regional simulation of ozone dry deposition is an important tool for understanding ozone pollution threats and quantifying the ozone impact on terrestrial ecosystems. In this study, we evaluate ozone dry deposition in the Yangtze River Delta (YRD) region using two different dry deposition schemes. The WRF-Chem model, Wesely dry deposition scheme, and revised Surfatm dry deposition scheme were used to simulate the ozone dry deposition process in the YRD region, and results are compared with the observation over a winter wheat field. The results show that the simulated ozone concentrations ( c O3 ) of the two dry deposition schemes were good and lower than the measurements. The simulated ozone dry deposition velocity ( V d ) in the Surfatm dry deposition scheme was more close to the measurements. The mean value of c O3 and V d in the YRD region ranged from 30 to 50 nL L −1 and from 0.2 to 0.5 cm s −1 in the daytime, respectively. To improve the simulation results of the ozone dry deposition process, the simulation errors due to different land use types, the parameters revisions as well as meteorological factors on dry deposition resistance functions, and the influence of chemical reactions must all be considered. Highlights: Simulations on ozone dry deposition were conducted in the Yangtze River Delta. Wesely and Surfatm ozone dry deposition schemes were chosen to simulate. Simulations were used to validated by measurements over a winter wheat field. Surfatm scheme showed better simulation performance.